Edukasi dan Konsultasi Hukum Kepada Tahanan di Lapas Pemuda Kelas IIA Tangerang - Herdycha Surya Kisworo; Sulaksono Sulaksono; Pudji Astuti (Jurnal Hukum Lex Generalis, 2025)
Community Service Program at Class IIA Tangerang Youth Correctional Facility aims to provide legal education and consultation to detainees regarding their rights, obligations, and applicable regulations. The results show improved legal understanding among most participants, although with varying levels of comprehension. This program represents an innovation expected to be implemented to enhance the quality of rehabilitation for Correctional Inmates